Analisis Gender dalam Cerita Rakyat (Kajian Semiotika Roland Barthes): Gender Analysis in Folklore (The Semiotic Study of Roland Barthes) - Siti Hardiyanti Amri (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
This paper studied about gender relation in two folklores entitled Tempiq Empiq from Nusa Tenggara Barat and Mencari Ilmu Berumahtangga from Kalimantan Selatan. The hierarchical relationship was analyzed by the semiological perspective of Roland Barthes. The research method consisted of data collection and data analysis. The primary data in this research was the folklores. Meanwhile, the secondary data was the written and electronic sources related to the socio-cultural and historical condition of Nusa Tenggara Barat and Kalimantan Selatan. The data was analyzed by the the theory and concepts of Barthes as the approach to find out the first and second order semiotic system revealing the myths related to the gender issues in the text. Afterwards, the myths contained in the text were connected to the specific intention, motivation, or ideology believed in particular culture or society as the background of the folklores. The research found that the analysis of linguistic system of the text revealed the dichotomy of roles and function between men and women. The analysis of connotative meaning found the myths of sexuality and masculinity which referred to patriarchal ideology.